Input switched single phase buck and buck-boost AC-DC converter with improved power quality - Khan, Mohammed Masum Siraj; Arifin, Md Shamsul; Hossain, Md Rubaiyat Tanvir; Kabir, Md Ashfanoor; Abedin, Amina Hasan; Choudhury, Mohammad Ali A Shoukat (© 2012 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2012 7th International Conference on Electrical and Computer Engineering, ICECE 2012; Dhaka; Bangladesh; 20 December 2012 through 22 December 2012 [© 2012 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/ICECE.2012.6471517